A global framework for climate action: orchestrating non-state and subnational initiatives for more effective global climate governance - Sander Chan; Pieter Pauw (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
The transformation towards a climate-resilient and low-carbon future will require collaboration between a host of institutions as well as state- and non-state stakeholders in addition to their numerous actions aimed at mitigation and adaptation. However, the “groundswell” of non-state and subnational actions and initiatives remains uncoordinated in a fragmented climate-governance landscape. This discussion paper investigates whether and how a Global Framework for Climate Action (GFCA) could become an advantageous link between the multilateral climate regime and non-state and subnational initiatives. It seeks to answer these questions by deriving lessons learnt from two case studies on existing frameworks that link non-state actions to multilateral processes: the Partnerships for Sustainable Development framework and the Private Sector Initiative under the UNFCCC Nairobi work programme on impacts, vulnerability and adaptation to climate change, respectively. The case studies show a disconnection between the recognition of the hard-to-deny potential of non-state and subnational initiatives, and the performance of the samples of initiatives that take part in the respective frameworks. The studied frameworks largely fail to capture effective initiatives. Moreover, the studied frameworks are not successful at ensuring credible information, transparency and progress by participating initiatives. The lack of screening procedures and minimal requirements for participating initiatives have made these frameworks vulnerable to green-washing practices in which business-as-usual passes for being climate-friendly and sustainable. Moreover, the investigated frameworks lack sufficient means to operate larger programmes to mobilise non-state and subnational stakeholders in the long-term. Based on lessons learnt, this discussion paper presents a design for a GFCA. The proposed GFCA is a comprehensive and collaborative programme. It is comprehensive, as it combines multiple functions, namely: the mobilisation of new and enhanced initiatives; the recording of initiatives in a publicly available registry; the monitoring and verification of progress; and the conducting of periodic overall assessments to ensure that the framework leads to higher ambitions and better implementation. A GFCA is collaborative, as it is operated and administered by a network of experts, think tanks, and public and private organisations rather than by a single administrative body. This network will yield the strengths of existing efforts and pool resources from multiple organisations, while retaining legitimacy through its partnership with international bodies such as the UNFCCC secretariat or UNEP. Moreover, by building on existing efforts, the GFCA would not require a heavy institutional footprint. The proposed GFCA could become an important element in the future global climategovernance architecture. On the one hand, this framework would strengthen the orchestration capacity within the UNFCCC to steer non-state and subnational actions towards greater ambitions and the implementation of international targets and agreements. On the other hand, a GFCA would entail official recognition of non-state and subnational initiatives that substantially contribute to low-carbon and climate-resilient development. A credible and well-designed GFCA would be an additional motivation for reputationconscious non-state stakeholders, such as businesses and NGOs, to participate.
Keywords: 330; Governance; Klimawandel